The use of social networking sites and their relation to the behavior of the university student - Walid, Djeboub (Journal of Humanities & Social Sciences, 2017)
This study aimed to show the extent of teenagers who represent students Tèbessa University contents of violence and crime that is seen or published or traded them through the media and communication affected, especially through social networking sites and networks, such as Facebook and stringing YouTube and Skype, etc., which may contribute to the formation and strengthening of behaviors negative in these through the following problem: Do you contribute to social networking sites through the implications of violence and crime in a negative impact on the behaviors of the students within the university community ?, also deliberately researcher to sample the estimated inventory of 50 students schooled at the Faculty of Economics and Commercial Sciences and Management Sciences of each section by an estimated 10% of the study population as a whole’s (2000) the adoption of simple random sampling technique, the results have also been addressing the adoption system (SPSS) , Which resulted in the results: the presence of a statistically significant correlation between the students’ use of social networking sites and the spread of deviant behavior within the university community?, And no statistically significant differences in the adverse effects of the use of social networking sites on the behavior of students depending on the sex variable, the largest of any female average for the benefit of, No statistically significant differences in the adverse effects of the use of social networking sites on the behavior of students depending on the variable physical level ?,No statistically significant differences in the adverse effects of the use of social networking sites on the behavior of the students due to the level of scientific student ?,The study also called attention to the recent media study the impact of the implications of violence and crime across social networking on the behavior of young people and adolescents sites, spreading awareness programs to help solve the problems of this phenomenon.